(untitled) (Jurnal Teknologi (Sciences & Engineering), 2022)
As a natural phenomenon, land movement does not occur suddenly, but it is a long-term phenomenon in the form of un-recoverable low rates deformation caused by constant stress on a slope body and known as creep. Therefore, it is very important to understand the rheological characteristics of the soil under constant stress and implication to its long-term strength and time dependent behavior of a soil mass. The laboratory shear creep tests were carried out on 15 undisturbed volcanic clay samples taken from the southern slopes of Lembang Village, Cililin, West Java, Indonesia. The tests were carried out by applying a constant shear stress level of 50% - 95% from the peak shear strength. The results show that the level of constant shear stress will affect to the rheological characteristics of the soil samples. The higher level of shear stress, the shorter failure time. Based on the shear creep tests, the rheological model was established, the failure time of the soil samples were estimated and the long-term strength equation was obtained. The long-term shear strength of the volcanic clay is decrease 52.38% from the peak shear strength and achieved after 925 days (±31 months). The cohesion (c) and internal friction angle (f) decrease from 41.548 kPa and 17.051o become 21.188 kPa and 9.129o, respectively. The shear creep test also shows that the soil shear strength parameters (c and f) are a function of time.